A Hybrid Recursive Model for Teaching and Learning Business Writing. Issue 1 (March 2013) - Schultz, Heidi
To replicate the need for communication speed and effectiveness in the workplace, I have designed a successful business writing course based on a hybrid recursive model that combines prescriptive rhetorical patterns with a perceptive application of those patterns. The model draws inspiration from (a) current-traditional rhetoric, modified for a business context, to address the need to write quickly, which I label the "prescriptive phase, " and from (b) cognitive rhetoric, again modified for a business context, to address the need to write effectively, which I label the "perceptive phase."